(untitled) (Handbook of Treatment Algorithms for Medical and Pharmacy Students, 2025)
Author Miss Hyndavi Trylockya Nagumantri, Pharm D Scholar, Koringa College of Pharmacy, Korangi, Tallarevu, Andhra Pradesh, India Abstract Endocrine disorder management involves correcting hormonal excesses or deficiencies to restore physiologic balance, with algorithms guided by laboratory thresholds and clinical targets. The algorithm for Type 1 Diabetes Mellitus is based on basal-bolus insulin replacement, with dosing calculated from carbohydrate intake and corrected for hyperglycemia. The Type 2 Diabetes algorithm is a stepwise, patient-centered approach beginning with lifestyle modification and metformin. Subsequent therapy is stratified by high-risk comorbidities, such as ASCVD, HF, or CKD, which prioritize SGLT2 inhibitors or GLP-1 receptor agonists. Thyroid disorder algorithms are distinct: hypothyroidism is managed with weight-based levothyroxine replacement, titrating the dose to a target TSH. Hyperthyroidism management is bifurcated by etiology, with Graves' disease treated via a three-pronged algorithm (beta-blockers for symptoms, anti-thyroid drugs, or definitive ablation/surgery), while nodular disease often requires ablation. Adrenal disorder algorithms are also specific: Addison's disease (insufficiency) requires lifelong glucocorticoid and mineralocorticoid replacement, whereas Cushing's syndrome (excess) requires a surgical algorithm to resect the causative tumor. The algorithm for Metabolic Syndrome is a multi-faceted approach focused on aggressive risk factor reduction, including weight loss and management of dyslipidemia and hypertension. Keywords: Endocrine Algorithms, Diabetes Mellitus, Thyroid Disorders, Adrenal Disorders, Metabolic Syndrome, Glycemic Control VIEW PDF